OPTIMIZATION OF TEACHER PEDAGOGICAL ABILITIES IN SHAPING THE ADAB OF ELEMENTARY SCHOOL - Muhammad Rafliyanto,; Fahrudin Mukhlis, (AULADUNA: Jurnal Pendidikan Dasar Islam, 2023)
Abstract Adab is an important foundation for the success of education as formulated in the Law on Indonesia's national education system in 2003. This article aims to describe in detail the forms of pedagogical optimization of educators in shaping the civilization of learners. This research is descriptive qualitative using a library research approach. The data analysis technique used in this research is the content analysis technique. The data source used in this research were from the pages of Google Scholar, Mendeley, Sinta, Chicago Journal, and Country Rank. The results of this research indicated three points, including: (1) designing a tawhid-based curriculum, (2) applying habituation methods in learning, and (3) carrying out monitoring and evaluation. The implication of this civilizational development process is the achievement of a process of national education goals that have long been formulated in the constitution of the Republic of Indonesia to form the faith and piety of students, so that a noble national civilization is formed.